Effect of market participation on the food and nutrition security status of the rural smallholder farmers: the case of Limpopo and Mpumalanga provinces, South Africa - Hlatshwayo, Simphiwe Innocentia; Ojo, Temitope Oluwaseun; Ngidi, Mjabuliseni Simon Cloapas (Frontiers in Sustainable Food Systems, 2023)
Hunger and malnutrition remain serious issues in developing countries, particularly in rural regions. Increased market participation of smallholder farmers can result in improved livelihood and nutrition outcomes. However, smallholder farmers encounter several obstacles that hinder their ability to participate in the market. As a result, the objective of this study is to investigate the factors that influence market participation and its impact on household nutrition security. The study relied on secondary data gathered from a sample size of 1520 people. About 389 of smallholder farmers participated in the market. The results from Food Consumption Score (FSC) cut-off points showed that in the overall sample households, 54% were within the acceptable food consumption diets (>35), while 30% and 16% were in the borderline (21.5-35) and poor diets (0-21), respectively. According to the Household Dietary Diversity Score (HDDS) findings, 57% of smallholder farmers in the total population sample consumed highly diverse diets (consisting of at least 6 food groups), while 25% and 18% of smallholder farmers consumed diets with medium dietary diversity (consisting of 4 to 5 food groups) and low dietary diversity (consisting of at most 3 food groups), respectively. The results from marginal analysis showed that gender of household head, receiving social grants and higher wealth index had a positive impact on market participation. The results from Poisson endogenous treatment effect model showed that household size, ownership of livestock, social grant, wealth index, access to market information and involvement in crop production had a positive and statistically significant impact on household nutrition security. On the other hand, agricultural assistance showed a negative and significant impact on household nutrition security. Providing nutrition education among smallholder farmers can help to raise awareness on the importance of nutrition security. More nutrition programmes and workshops that need to be conducted in rural areas to help smallholder farmers on improving their nutrition security status.